Self-bonding sandwiched membranes from PDMS and cellulose nanocrystals by engineering strategy of layer-by-layer curing. (16th June 2018) - Xia, Tao; Yuwen, Hongjuan; Lin, Ning
Abstract: Multilayer materials attracted intense scientific interests in view of their special interlayer structure and potential application in diverse fields. Different from the conventional approach of layer-by-layer assembly, in this study we proposed an engineering approach of layer-by-layer curing from polydimethylsiloxane (PDMS) elastomer and rigid cellulose nanocrystals (CNC). The covalent-bonding from the crosslinking curing reaction as the driving force ensured the strong interlayers adhesion, and meanwhile the nanoreinforcing effect from silylated CNC in the composite layers provided the tailor-made physicochemical properties for the fabricated multilayer membranes. The multilayer structures indicating the good interlayers' adhesion and structural integrity of the di- and tri-layer membranes were observed from the microscopy characterization. In comparison with the monolayer PDMS membrane, the developed CPC trilayer membrane (possessing the sandwiched structure of two composite layers and one neat layer) exhibited the advancement on the storage modulus, special optical scattering and hazing, dielectric permittivity and barrier performance, derived from the nanoscaled reinforcing and obstruction effects of rod-like natural nanoparticles (SiCNC).